Sub-Maximal Exercise Altered the Prednisolone Absorption Pattern. - Kuei-Yu Chien; Ting-Ting Chen; Jia Hsu; Ryh-Nan Pan; Jih-Heng Li; Chia-Hua Kuo; Mei-Chich Hsu (Frontiers Media S.A., 2010)
PURPOSE: Prednisolone has been widely used due to its relatively short pituitary inhibition and its moderate potency. Exercise is one of the non-pharmacological interventions for glucocorticoid- induced osteoporosis prevention. However, the effects of exercise on the pharmacokinetics of prednisolone were unclear. The purpose of this study was to evaluate the effects of sub-maximal exercise on the pharmacokinetics of prednisolone. METHODS: A randomized, double-blind, cross-over experimental design was used. Subjects needed to undertake two trials: a non-exercise trial (NE) and an exercise trial (E). After the first blood sampling, the subjects consumed 5mg of prednisolone with 100mL of water and then took a rest for 30 min. In the E trial, subjects cycled at 70% VO2max intensity until exhaustion. When subjects underwent the NE trial, they remained seated for the duration of the experiment. Serial blood samples were collected at 0.25, 0.5, 0.75, 1, 1.25, 1.5, 2, 3, 4, 5, 6, 8, 10 and 12h after prednisolone administration. Prednisolone and cortisol concentration were analyzed with a validated high performance liquid chromatographic method. RESULTS: This study indicated that the maximum concentration of the E trial was significantly lower than the NE trial (p